A rare case of childhood polyarteritis nodosa successfully treated with etanercept - Kamath, Pragathi; Verma, Bela; Sawant, Tejasi (International Journal of Research in Medical Sciences, 2019)
Childhood Polyarteritis Nodosa (CPAN) a rare and often fatal disease tends to be more common in individuals of Asian descent. Previously it was referred to as Infantile PAN. Polyarteritis Nodosa (PAN) is a systemic autoimmune vasculitis characterized by necrotizing inflammatory lesions of the medium-sized and small muscular arteries, preferentially at vessel bifurcations, resulting in formation of microaneurysms, aneurysmal ruptures with hemorrhage, thrombosis and consequently organ ischemia or infarction. It usually appears in middle or older age without gender predilection. PAN shows variety of symptoms, including general symptoms, neurological, skin, renal and gastrointestinal involvement. In particular skin lesions characterized by multiple firm waxy papules, subcutaneous nodules, livedo reticularis, ulcers and gangrene are observed in 25%-60% of patients with PAN. The etiology of systemic vasculitis is yet unknown. However, dysregulation and/or enhanced expression of pro-inflammatory substances may be involved in pathogenesis of these diseases. Tumour necrosis factor (TNF) alpha is a pro-inflammatory cytokine produced primarily by cells of macrophage-monocyte lineage which may directly participate in vascular inflammation as well as in endothelial cell death via apoptosis. In addition, TNF-alpha may play a role in neutrophil priming inducing membrane expression of Proteinase-3 or Myeloperoxidase which are subsequently recognized by ANCA-associated vasculitis (AAV). Author report a case of 14 months old male child with complaints of fever, gangrenous changes of ear lobes, tip of nose and toes, seizures, altered sensorium and hypertension. Initially Injectable Methyl Prednisolone pulse therapy was started followed by oral Prednisolone. After initiation of Etanercept treatment, his symptoms improved dramatically. Sensorium improved, skin ulcers healed faster, and gangrenous changes were arrested, fever subsided and child started accepting oral feeds.